2015
DOI: 10.1097/aog.0000000000000750
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Preparedness in Obstetrics

Abstract: During and after disasters, focus is directed toward meeting the immediate needs of the general population. As a result, the routine health care and the special needs of some vulnerable populations such as pregnant and postpartum women may be overlooked within a resource-limited setting. In the event of hazards such as natural disasters, manmade disasters, and terrorism, knowledge of emergency preparedness strategies is imperative for the pregnant woman and her family, obstetric providers, and hospitals. Indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Hospitals preparedness planning should not overlook the special needs of pediatric, obstetric, and geriatric populations. [20][21][22][23] A US study from 2008 showed that less than one-half of hospitals could accommodate the needs for persons with disability during disasters. 24 Those populations represent a considerable percentage of the Makkah region.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals preparedness planning should not overlook the special needs of pediatric, obstetric, and geriatric populations. [20][21][22][23] A US study from 2008 showed that less than one-half of hospitals could accommodate the needs for persons with disability during disasters. 24 Those populations represent a considerable percentage of the Makkah region.…”
Section: Discussionmentioning
confidence: 99%
“…Emergencies and natural disasters stress a healthcare system and lead to challenges in protecting patients' and providers' welfare [2,3,5,6]. Hospitals and other healthcare systems need to protect patients, employees, and physical resources during such events while continuing to provide care to those in need.…”
Section: Types Of Emergenciesmentioning
confidence: 99%
“…Planning for an emergency necessitates the creation of emergency preparedness checklists to address several key requirements: 1) Patient notification systems (in case of emergency or closure); 2) Staff notification system (in case of emergency or closure); 3) Medical records backup plan (e.g., cloud servers for electronic records, short term use of paper records); 4) Remote medical record access, 5) Billing services (continuity plan); 6) Security at the facility; 7) Utility emergency shut-off location and procedures; 8) Service availability (define available priority services); 9) Disaster planning for staff (who is expected to work and when) [5].…”
Section: Assessing Emergency Needs and Equipmentmentioning
confidence: 99%
“…In countries where pregnant women are among the most vulnerable groups after disasters, an emergency preparedness plan for pregnant women at family and community levels can provide maternal care support to pregnant women after disasters. Creating home delivery plans, promoting group support and training community health workers are some components of emergency preparedness plans for maternal care after disasters (Haeri & Marcozzi, 2015).…”
Section: By Eva Chor-chiu Lammentioning
confidence: 99%